2012
DOI: 10.1016/j.econlet.2012.04.077
|View full text |Cite
|
Sign up to set email alerts
|

Unwillingness to pay for privacy: A field experiment

Abstract: We measure willingness to pay for privacy in a field experiment. Participants were given the choice to buy a maximum of one DVD from one of two online stores. One store consistently required more sensitive personal data than the other, but otherwise the stores were identical. In one treatment, DVDs were one Euro cheaper at the store requesting more personal information, and almost all buyers chose the cheaper store. Surprisingly, in the second treatment when prices were identical, participants bought from both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(130 citation statements)
references
References 7 publications
6
117
2
5
Order By: Relevance
“…the higher the money involved, the greater the need to collect personally identifiable information of participants and hence, the lesser the privacy. This is further supported by evidence from a previous study [58] suggesting that money can quickly incentivise people to forgo their privacy. More specifically, the study found that people are willing to provide sensitive information about themselves for as low as 1 Euro [58].…”
Section: Privacysupporting
confidence: 74%
“…the higher the money involved, the greater the need to collect personally identifiable information of participants and hence, the lesser the privacy. This is further supported by evidence from a previous study [58] suggesting that money can quickly incentivise people to forgo their privacy. More specifically, the study found that people are willing to provide sensitive information about themselves for as low as 1 Euro [58].…”
Section: Privacysupporting
confidence: 74%
“…This is particularly the case as work such as Beresford et al (2010) has found little empirical evidence of privacy concerns when it comes to choosing a vendor, though other research such as Acquisti and Spiekermann (2011) has found that interruptive advertising can reduce willingness-to-pay by consumers in a lab setting.…”
Section: Does Consumers' Distaste For 'Intrusiveness' Matter Empiricamentioning
confidence: 95%
“…Acquisti and Grossklags (2005) found that 89.2 percent of their survey respondents identified themselves as moderately or very concerned about privacy, but 28.6 percent admitted to revealing their phone numbers for discounts or better services and 21.8 percent admitted to doing the same with their social security number. Similarly, Beresford, Kübler, and Preibusch (2012) found that although 75 percent of their subjects indicated a strong interest in data protection, when they purchased a DVD from one of two competing online stores, they were willing to provide income and date-ofbirth information at one store for a mere one-euro discount and, even when prices at the two stores were the identical, seemed to give virtually no premium to the privacy-friendly vendor.…”
Section: Studying the Perceived Value Of Transparency And Privacymentioning
confidence: 99%